CONSISTENT TERMINOLOGY IN ASTRONOMY TRANSLATIONS - Khafiza Mukhtorova (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: Consistent terminology is crucial in astronomy translations to ensure effective communication and understanding across different languages. This article delves into the significance of maintaining uniformity in translating astronomical terms and explores the challenges encountered in this process. By examining the importance of clear and accurate scientific communication, the article highlights the need for precise terminology in the field of astronomy. It discusses the obstacles faced by translators, such as achieving conceptual equivalence, navigating cultural and linguistic differences, handling neologisms and metaphors, maintaining consistency, and upholding technical accuracy. The article emphasizes the collaborative efforts required among astronomers, linguists, and translators to establish standardized glossaries and guidelines. It also provides examples of how astronomical terms are translated across languages and cultures, showcasing the variations and adaptations that arise. Ultimately, consistent terminology enables global collaboration, preserves scientific accuracy, facilitates comparative studies, supports education and outreach initiatives, and respects the cultural identity of different language communities.